Investigating Media Impact on Shaping Public Opinion Towards Terrorism Case study: post 9/11 attacks - Kelouche ,Mebarka; Tahari, Amina; Ben Redda ,Djamel (University of Ammar Theledji -Laghouat, 2020)
The present study attempts to depict media coverage of information and their response towards 9/11 attacks, and the common interest–game between U.S. government and media. The events of September 11th shaped rather than changed contemporary history. The 9/11 events were shocking global media events that has a relation to the global public attention. These media spectacles were intended to open a terror spectacle. The world media cover the 9/11 event as a global tragedy especially the American media who convinced the whole world that the 9/11 attacks were an act of war against America, where it holds ambiguity until the present day. The main objective of this research work is to investigate the American media role in shaping public opinion and to analyse the world’s media response to the 9/11 attacks, and how did this tragedy change the American media construction under the umbrella of the following hypotheses: different world’s media and especially the American ones have greatly affected the opinion of the whole world after 9/11, as well as, the change that took place in media reports about terrorism and the concept of Islamophobia. In addition, this study will adopt an online questionnaire to investigate research questions and support our hypotheses. The findings showed that the majority of participants had negative opinions about the media coverage of the 9/11 attacks. Which can be labeled as normal response since they support our hypotheses .However the rest minority answered in the favour of the 9/11 American media objectivity coverage. In which they represent the affected category with media manipulations